Ethnic Politics of Russian Empire - Dadeshkeliani-Aprasidze, Bimurza (Actual Problems of Kartvelology, 2019)
Russian Empire had always been fighting against Georgian sovereignty with the use of different theories and concepts and this fight continues to these days. It must be noted, that concept of Sakharov – „Georgia – Little Empire“ was in full accordance with the plans of Russian Empire architects – Alexander I, Nicholas I, Decembrists, Alexander II, Stalin, Gorbachev, Primakov, Dugin, Putin, Zhirinovsky. In 19th century Russian Empire decided to completely remove local population from entire coast spanning from river Kuban to town Poti and instead settle Russian military personnel there. This plan was carried out by Alexander I and Alexander II by conducting the genocide and mass-deportation against local population. With these methods entire coast of Sochi-Adler-Tuapse was cleansed from Circassians and Ubykhs, they were deported to Turkey. The same methods of cleansing were used for the coastal settlements of Abkhazia. it shall be said, that Kremlin fake-news machine often insinuated for the purpose of discrediting national government. These incidents were often reported by western media and diplomacy as true. To name one: In 1991 influential French newspaper „Le Monde“ printed, that Gamsakhurdia issued the law in Georgia, which prohibited Ossetians to have more than one child! After several years, when Editor of this newspaper was asked by upset Georgians, what was the source of such news, he replied that informer was somebody he trusted very much, this person was Merab Mamardashvili.